2023
DOI: 10.1002/smll.202302575
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Ferroptosis and Apoptosis Facilitated by Differentiation Therapy Efficiently Suppress the Progression of Osteosarcoma

Abstract: Osteosarcoma (OS) is the most frequent osseous neoplasm among young people aged 10–20. Currently, the leading treatment for osteosarcoma is a combination of surgery and chemotherapy. However, the mortality remains high due to chemoresistance, metastasis, and recurrence, attributing to the existence of cancer stem cells (CSCs) as reported. To target CSCs, differentiation therapy attracts increasing attention, inducing CSCs to bulk tumor cells with elevated reactive oxygen species (ROS) levels and less chemoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Therefore, the additive effect of ferroptosis activation on the anti-tumoral effect of chemotherapeutic agents on cell viability can be of interest and open a new era in cancer medicine. Recent findings have evaluated the efficacy of biomimetic/biocompatible formulations and pH-responsive liposomal nanoreactors for inducing ferroptosis in cancer models [ 107 , 108 ].…”
Section: Ferroptosis In Cancermentioning
confidence: 99%
“…Therefore, the additive effect of ferroptosis activation on the anti-tumoral effect of chemotherapeutic agents on cell viability can be of interest and open a new era in cancer medicine. Recent findings have evaluated the efficacy of biomimetic/biocompatible formulations and pH-responsive liposomal nanoreactors for inducing ferroptosis in cancer models [ 107 , 108 ].…”
Section: Ferroptosis In Cancermentioning
confidence: 99%
“…Zhao et al 136 The apoptotic anticancer mechanism involves the activation of cytochrome c, which initiates mitochondrial apoptosis, while ferroptosis is initiated by NCOA4. 122 He et al 138…”
Section: Enhancing Sensitivity To Os Chemotherapy Through Ferroptosismentioning
confidence: 99%
“…Inducing ferroptosis was thought to enhance the effects of 'traditional' anti-cancer treatments that trigger other cell death pathways, mostly apoptosis. Multiple studies had shown that simultaneous targeting of apoptosis and ferroptosis can effectively bypassing chemoresistance, which was an effective strategy to inhibit OS cells [18][19][20][21]. Oridonin was reported to exhibit the anti-tumor activity via inducing ferroptosis in gastric cancer and esophageal cancer [22,23].…”
Section: Introductionmentioning
confidence: 99%